An Ethnoarchaeological Discussion of the Impact of Religion on Architecture in a Remote Iranian Village - Tahere Rahimkhani (EXARC Journal)
In the years 2014 to 2015, an Ethnoarchaeological study of the architecture of Makhunik village (Doreh Rural District, in the Central District of Sarbisheh County, South Khorasan Province, Iran) was done (Rahimkhani 2015). After that, this architecture was studied in different points of view. One of these views was the influence of religion on the architecture of the traditional phase (ca. 1660-1960) to explore the impact of immaterial issues, such as religion in a very religious village, on material issues such as architecture. Both the Islamic writings and Quran was used to develop expectations of what a religiously-influenced architecture would look like, then it was compared to architecture as documented in the field, also taking into account additional factors that influenced the construction of the houses (e.g., landscape affordances and historical context). I concluded that despite the strong influence of religion in all aspects of people's lives, it probably has had a very limited impact on village architecture and layout.